2012
DOI: 10.1007/s10646-011-0808-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and genotoxicity of organic and inorganic nanoparticles to the bacteria Vibrio fischeri and Salmonella typhimurium

Abstract: The present work aimed at evaluating the toxicity and genotoxicity of two organic (vesicles composed of sodium dodecyl sulphate/didodecyl dimethylammonium bromide-SDS/DDAB and of monoolein and sodium oelate-Mo/NaO) and four inorganic (titanium oxide-TiO₂, silicon titanium-TiSiO₄, Lumidot-CdSe/ZnS, and gold nanorods) nanoparticles (NP), suspended in two aqueous media (Milli Q water and American Society for Testing and Materials (ASTM) hardwater), to the bacteria Vibrio fischeri (Microtox test) and Salmonella ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 46 publications
5
30
0
2
Order By: Relevance
“…These results were in agreement with those reported by other authors, which till now have recorded no mutagenicity potential of different nanosize metal oxides (Al 2 O 3 , Co 3 O 4 , TiO 2 , ZnO, and Fe 3 O 4 ) to S. typhimurium and E. coli, both in the absence and presence of metabolic activation (Pan et al 2010;Pereira et al 2011;Lopes et al 2012;Szalay et al 2012). However, although the nano-TiO 2 tested in our study was smaller (<25 nm) than those used in previous studies, in Milli Q water (dilution medium in the Ames test), this nanooxide formed aggregates higher than 500 nm in diameter (Table 2), and this could have not favored the cellular uptake and the access to genetic material.…”
Section: Discussionsupporting
confidence: 93%
“…These results were in agreement with those reported by other authors, which till now have recorded no mutagenicity potential of different nanosize metal oxides (Al 2 O 3 , Co 3 O 4 , TiO 2 , ZnO, and Fe 3 O 4 ) to S. typhimurium and E. coli, both in the absence and presence of metabolic activation (Pan et al 2010;Pereira et al 2011;Lopes et al 2012;Szalay et al 2012). However, although the nano-TiO 2 tested in our study was smaller (<25 nm) than those used in previous studies, in Milli Q water (dilution medium in the Ames test), this nanooxide formed aggregates higher than 500 nm in diameter (Table 2), and this could have not favored the cellular uptake and the access to genetic material.…”
Section: Discussionsupporting
confidence: 93%
“…perezi tadpoles which agrees with Pereira et al (2011) and Lopes et al (2012), who found no toxic effects of TiSiO 4 -NP to V. fisheri. Nevertheless, tadpoles' exposure to TiSiO 4 -NP revealed biochemical and metabolic effects.…”
supporting
confidence: 90%
“…Pelophylax perezi was used because inhabits permanent water bodies widespread in Iberian Peninsula and Southern France, is abundant, have not a protection status and is not endangered (Llorente and Arano, 1997). Titanium-based NP were chosen because are commonly used in several consumer products (Li et al, 2010), and, to our knowledge, only three studies were published with TiSiO 4 -NP (Pereira et al, 2011;Lopes et al, 2012;Nogueira et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanopartículas são substâncias com pelo menos uma das dimensões medindo entre 1 e 100 nanômetros (nm) (MOORE, 2006;HANDY et al, 2008b;LOPES et al, 2012 A produção e a variedade destes produtos vêm crescendo rapidamente, assim como o crescimento da nanotecnologia, uma engenharia que abrange o desenvolvimento e a utilização destas substâncias (DAUGHTON, 2004;MOORE, 2006;HANDY et al, 2008;SINGH et al, 2009 A contaminação por nanopartículas nos organismos aquáticos pode ocorrer através da ingestão direta e também através da interface epitelial, tais como brânquias, órgão olfatório ou parede corporal. Além disso, organismos aquáticos desenvolvem processos de alta eficiência, como endocitose e fagocitose, para ingestão de partículas em escala nano e micrométrica (CANESI et al, 2008).…”
Section: Introductionunclassified